Hierarchical Sb2S3/ZnIn2S4 core–shell heterostructure for highly efficient photocatalytic hydrogen production and pollutant degradation - Xiao, Yan; Wang, Hao; Jiang, Yinhua; Zhang, Wenli; Zhang, Jianming; Wu, Xiangyang; Liu, Zhanchao; Deng, Wei (Journal of colloid and interface science, 2022)
A novel ZnIn2S4 decorated Sb2S3 hierarchical 1D/2D core–shell heterostructure was successfully fabricated by a simple hydrothermal method. It possessed highly efficient photocatalytic activities of hydrogen evolution and pollutant degradation. This work will provide a novel dual-function core–shell heterostructure photocatalyst to solve environmental pollution and produce hydrogen energy. [Display omitted] In this work, a novel hierarchical 1D/2D core/shell Sb2S3-ZnIn2S4 (SB-ZIS) heterostructure with highly efficient photocatalytic activities for both hydrogen production from water and organic pollutant degradation was designed and fabricated via a simple one-step hydrothermal method. The as-prepared SB-ZIS heterostructure, where ZnIn2S4 nanosheets uniformly grew onto Sb2S3 nanorod to form a tight and large intimate contacted interface, was conducive to improve the absorption capacity of light, increase the surface area, shorten the distance of electronic transmission channels and accelerate the separation and migration of photogenerated carriers. As a result, the presented SB-ZIS composites demonstrated significantly enhanced photocatalytic performances for H2 generation and Tetracycline Hydrochloride (TCH) photodegradation. The photocatalytic H2 production rate of optimal SB-ZIS-2 sample (1685.14 μmol·g−1·h−1) was about 12.24 times as large as that of pure ZnIn2S4 (137.63 μmol·g−1·h−1). The apparent quantum efficiency (AQE) at 420 nm was up to 3.8%. In addition, the highest rate constant for TCH removal (0.514 h−1) was 20.3 and 2.89 times larger than those of pure Sb2S3 and Znln2S4, respectively. The possible reaction routes of TCH and the photocatalytic reaction mechanism of SB-ZIS sample were also discussed in detail. This work will provide some useful information for the development of dual-functional Sb2S3-based type I core–shell heterostructure with an efficient photocatalytic activity for solving environmental pollution and producing clean hydrogen energy.